2019
DOI: 10.1088/1755-1315/341/1/012163
|View full text |Cite
|
Sign up to set email alerts
|

Fertility of ewe following intrauterine laparoscopic insemination with frozen-thawed semen

Abstract: Cryopreservation of sperm opening up possibilities for improvement of breeding work due to the rational use of the valuable animals’ genetic potential became the basis for cryobanks of biomaterial, contributed to the widespread, the exchange of gene pool. However, AI with frozen-thawed semen is not widespread in sheep as it is in other domestic species. One reason for this is the low efficiency of frozen-thawed ram semen application. The aim of research was to study the fertilizing ability of frozen-thawed sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…As expected, LR reported in simple statistics of our study were nearly half to those performed under a precise heat detection as was reported by McCappin and Murray, 2011 , Fair et al, 2005 , Anel et al, 2005 , or Masoudi et al (2017) . Interestingly, very similar results to ours were reached previously by Aybazov et al, who in line with our methodology investigated LR of LAI-ed ewe once-daily detected in natural heat ( Aybazov et al, 2019 ). In agreement with Schakell et al, 1990 , Cseh et al, 2012 , our results confirmed that the time of insemination after heat detection impacts significantly the subsequent LR.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…As expected, LR reported in simple statistics of our study were nearly half to those performed under a precise heat detection as was reported by McCappin and Murray, 2011 , Fair et al, 2005 , Anel et al, 2005 , or Masoudi et al (2017) . Interestingly, very similar results to ours were reached previously by Aybazov et al, who in line with our methodology investigated LR of LAI-ed ewe once-daily detected in natural heat ( Aybazov et al, 2019 ). In agreement with Schakell et al, 1990 , Cseh et al, 2012 , our results confirmed that the time of insemination after heat detection impacts significantly the subsequent LR.…”
Section: Discussionsupporting
confidence: 92%
“…Evans and Maxwell (1987) stated that accurate knowledge of the time of ovulation is crucial to the success of insemination and that in the field conditions accurate detection of heat onset in ewes with natural heat is problematic. Twice daily heat detection allows more accurate timing of insemination relatively to ovulation ( Aybazov et al, 2019 , Evans and Maxwell, 1987 ), and it was used for intrauterine ( Aybazov et al, 2019 , Ham et al, 2000 ) or cervical ( Aybazov et al, 2019 , Paulenz et al, 2004 ) inseminations with thawed sperm of ewes in natural heat. Another approach is inducing heat cycle using a hormonal program ( De et al, 2015 , Casali et al, 2017 , Gibbons et al, 2019 , Macías et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, pregnancy outcome was greater when compared to intravaginal insemination. In fact, reported results range between 17% and 31.25% (Maxwell and Hewitt 1986;Anel et al 2005) for intravaginal insemination, 18.4% and 34.4% for cervical insemination (Maxwell and Hewitt 1986;Aybazov et al 2019), 13.7% and 34.8% for TCAI (Halbert et al 1990;Eppleston and Maxwell 1995;Salamon and Maxwell 1995a). Indeed, by using laparoscopic intrauterine insemination higher PR is obtained, that is around 44.8% (Anel et al 2005), 50.2% (Casali et al 2017) and 63.7% (Pau et al 2019).…”
Section: Resultsmentioning
confidence: 99%